(untitled) (Journal of International Studies, 2020)
Many Malaysian companies with business activities in the Asia Pacific region have strategic alliances with local companies. An exploratory overview of their strategic orientation and performance reveals that they are mostly local market oriented, and their success is closely associated with three factors; working relationships with partners, difficulties in partnering agreements, and difficulties arising from environment and cultural differences. These three factors remain important regardless of the varying objectives, motives and opinions concerning the benefits and governance of the alliances.